2011
DOI: 10.1111/j.1752-8062.2011.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Research Mentors Working in the Area of Clinical Translational Science: A Review of the Literature

Abstract: The goal of this paper is to review the evaluation of mentors with a focus on training new investigators in clinical translational science. These scholars include physicians and PhD scientists who are generally assistant professors in clinical departments. This white paper is one of a series of articles focused on the programmatic elements of effective mentoring practices and the “current state of the art”. Evaluating mentor performance and providing formative feedback can lead to stronger mentoring and ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…Some metrics for mentors have been developed, such as those reviewed in Meagher et al [74] and those developed for use in a recent randomized controlled trial of a mentor training intervention [35, 75]. Metrics focusing on mentee gains from mentoring relationships and research experiences include the undergraduate research student self-assessment [76] and the survey of undergraduate research experiences [77].…”
Section: Metrics For Assessing Mentors Mentees and Mentoring Relatiomentioning
confidence: 99%
“…Some metrics for mentors have been developed, such as those reviewed in Meagher et al [74] and those developed for use in a recent randomized controlled trial of a mentor training intervention [35, 75]. Metrics focusing on mentee gains from mentoring relationships and research experiences include the undergraduate research student self-assessment [76] and the survey of undergraduate research experiences [77].…”
Section: Metrics For Assessing Mentors Mentees and Mentoring Relatiomentioning
confidence: 99%
“…Entering Mentoring has grown into a highly sophisticated and rapidly expanding workshop-based approach to developing skills of mentors and promoting effective mentoring relationships. A strong research base supporting this approach is emerging, including a randomized controlled trial conducted at 16 academic health centers across the U.S. (9-13). A recent independent qualitative study with mentors of junior faculty at two academic medical centers identified essentially the same attributes as those in Entering Mentoring and its subsequent expansions (14).…”
Section: Recent Research On Approaches To and Attributes Of Effectivementioning
confidence: 99%
“…Despite a relative dearth of quantitative evaluation of team mentoring experiences, team mentoring continues to be a critical element of training programs for the inter- and transdisciplinary research work force. While there are validated tools to evaluate the individual mentor-mentee relationship, 2427 it is not known whether being mentored by teams further amplifies these positive findings of mentoring or has negative effects.…”
mentioning
confidence: 99%